Phenolic Composition, Anti-Inflammatory, Antioxidant, and Antimicrobial Activities of Alchemilla mollis (Buser) Rothm. - Karatoprak, Gokce Seker; Ilgun, Selen; Kosar, Muberra (Wiley-V C H Verlag Gmbh, 2017)
The current study was designed to evaluate the antioxidant, anti-inflammatory and antimicrobial activities of Alchemilla mollis (Buser) Rothm. (Rosaceae) aerial parts extracts. Chemical composition was analyzed by spectrophotometric and chromatographic (HPLC) techniques. The antioxidant properties assessed included DPPH and ABTS(+) radical scavenging, -carotene-linoleic acid co-oxidation assay. Antimicrobial activity was evaluated with disc diffusion and micro dilution method. In order to evaluate toxicity of the extracts, with the sulforhodamine B colorimetric assay L929 cell line (mouse fibroblast) was used. The anti-inflammatory activities of the potent antioxidant extracts (methanol, 70% methanol, and water extracts) were determined by measuring the inhibitory effects on NO production and pro-inflammatory cytokine TNF- levels in lipopolysaccharide stimulated RAW 264.7 cells. 70% methanol and water extracts which were found to be rich in phenolic compounds (184.79 and 172.60 mg GAE/g extract) showed higher antioxidant activity. Luteolin-7-O-glucoside was the main compound in the extracts. Ethyl acetate and 70% methanol extracts showed higher antibacterial activity against Staphylococcus aureus and Salmonella enteritidis with MIC value of 125 g/ml. 70% methanol extract potentially inhibited the NO and TNF- production (18.43 m and 1556.22 pg/ml, respectively, 6 h).
Keywords: Alchemilla mollis; Rosaceae; HPLC; Anti-inflammatory activity; Antioxidant activity; Antimicrobial activity